2019
DOI: 10.4103/jfmpc.jfmpc_167_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smoking among dental students and gauging their knowledge about tobacco cessation methods: An original study

Abstract: Aims: The aims of this study are to determine the prevalence and type of tobacco use among dental students and to identify the factors that influence them to initiate tobacco use. Subjects and Methods: Dental students at two dental colleges affiliated to State Health University of Kerala answered a 20-item questionnaire during Jan–Feb 2015 that investigated their smoking habits and knowledge about the risk factors of smoking habits. The questions were based on the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
(7 reference statements)
4
10
1
1
Order By: Relevance
“…This is an alarming result, as both study groups of dental students presented a smoking incidence higher than the general Egyptian population [ 42 ] and Egyptian medical students [ 43 ], and ranked among the highest rates worldwide [ 3 , 44 ]. In contrast to student groups in Japan [ 45 ], India [ 46 ], and Germany [ 3 ], the current survey displayed higher smoking rates among preclinical than clinical participants. This observation was explained in previous studies on medical and dental students, as higher levels of education or clinical knowledge were positively correlated with a cessation of tobacco-associated habits or the consumption of other psychoactive substances [ 47 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 82%
“…This is an alarming result, as both study groups of dental students presented a smoking incidence higher than the general Egyptian population [ 42 ] and Egyptian medical students [ 43 ], and ranked among the highest rates worldwide [ 3 , 44 ]. In contrast to student groups in Japan [ 45 ], India [ 46 ], and Germany [ 3 ], the current survey displayed higher smoking rates among preclinical than clinical participants. This observation was explained in previous studies on medical and dental students, as higher levels of education or clinical knowledge were positively correlated with a cessation of tobacco-associated habits or the consumption of other psychoactive substances [ 47 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Within our sample, one in five students reported being occasional or regular smokers. This proportion is within the range of smoking prevalence reported for dental students in various countries (Brazil: 8.9%; India: 17%; Romania: 37%). In 2011, the Global Health Professions Student Survey provided the most comprehensive overview of smoking prevalence in dental students to date.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, out of 88 participants, 26 were tobacco users of which 20 (44.4%) were males and 6(13.9%) were females. A similar study among dental students by Thomas (2019) revealed that boys were 3.15 times more likely to use tobacco compared to girls. 13 In the present study stress and friends (peer pressure) were the principle reasons for tobacco usage.…”
Section: Discussionmentioning
confidence: 81%
“…A similar study among dental students by Thomas (2019) revealed that boys were 3.15 times more likely to use tobacco compared to girls. 13 In the present study stress and friends (peer pressure) were the principle reasons for tobacco usage. A similar study in Saudi Arabia revealed that the effect of having close friends that smoke along with high stress might increase the rate of smoking among medical interns in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 81%